2020
DOI: 10.18632/aging.103397
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal famine exposure and estimated glomerular filtration rate across consecutive generations: association and epigenetic mediation in a population-based cohort study in Suihua China

Abstract: Prenatal malnutrition could promote renal dysfunction in adulthood, but it is unclear whether the detrimental effect could be transmitted to the next generation. We investigated whether famine exposure was associated with variation of estimated glomerular filtration rate(eGFR) in two generations and explored the mediation role of methylation alterations. The longitudinal analysis included 2909 participants from Suihua rural area. F1 and F2 generations were divided into non-famine and famine group based on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…However, only few longitudinal studies were conducted to investigate the long term consequence of perinatal famine on kidney function. Nonetheless, the available studies conducted among Chines and the Dutch famine survivors reported higher risk of CKD and or suboptimal kidney functional markers such as protein urea among prenatal famine exposed groups [11][12][13][14]21].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, only few longitudinal studies were conducted to investigate the long term consequence of perinatal famine on kidney function. Nonetheless, the available studies conducted among Chines and the Dutch famine survivors reported higher risk of CKD and or suboptimal kidney functional markers such as protein urea among prenatal famine exposed groups [11][12][13][14]21].…”
Section: Introductionmentioning
confidence: 98%
“…Atypically, common etiologies in low-income countries have been documented as diarrheal diseases, HIV infection, low birth weight, malaria and preterm birth [2,3]. Furthermore, data in recent decades also showed correlations between suboptimal kidney health among adults and their childhood adverse events such as prenatal famine exposure [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, only few longitudinal studies were conducted to investigate the long term consequence of perinatal famine on kidney function. Nonetheless, the available studies conducted among Chines and the Dutch famine survivors reported higher risk of CKD and or suboptimal kidney functional markers such as protein urea among prenatal famine exposed groups [11][12][13][14]22].…”
Section: Introductionmentioning
confidence: 98%
“…Atypically, common etiologies in low income countries have been documented as diarrheal diseases, HIV infection, low birth weight, malaria and preterm birth [2][3]. Furthermore, data in recent decades also showed correlation between suboptimal kidney health and contextual risk factors such as prenatal unhealthy environment [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, a limited number of longitudinal studies were done to investigate the long term consequence of perinatal famine on the kidney function. Yet, the available studies, conducted among Chines and the Dutch famine survivors reported an increased risk of CKD and or suboptimal kidney functional markers such as protein urea among prenatal famine exposed groups [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%